A Real-Time Implementation of Air Audit System for Compressors towards Energy Conservation: An Industrial Case Study. (20th June 2022) - Loganathan, Ashok Kumar; Alexander Stonier, Albert; Uma Maheswari, Y.; Peter, Geno; Samraj Lawrence, T.
Abstract : The air audit system is designed for enabling sales engineers to capture customer's requirement of the compressed air system. This system is required to create quick audit solution to support customers by estimating air consumption. It also educates the customers with potential improvement areas after understanding their existing demand pattern. At present, many industries and manufacturers are using third-party air audit tools. Many leading manufacturers of air compressors in accordance with the core values of the company intend to develop their own air audit system. The problem statement is to understand the air demand pattern with respect to flow and pressure, capture the existing power consumption details, and select the optimum compressor size based on the demand pattern. The air audit methodology involves data logging process, data transfer, and report generation. The data logging process includes measuring current, voltage, and true power of each compressor, tank pressure with logging frequency of minimum 5s, and data logging period of minimum seven days. The data will be transmitted to a mobile or tab over WiFi. A mobile GUI (graphical user interface) will be developed to generate the report and graph. All received data will be stored in a cloud database. The paper presents a proof of concept for the air audit system by tapping signals from the existing power quality analyzer, feeding it to a microcontroller, processing it, performing data logging, transferring the bulk data through WiFi upon request to the company or consumer, graphically presenting the data through a mobile app, and report generation. This work can also be extended by developing a battery-operated standalone module for air auditing which will be provided for the sales engineer and the customers. The overall need for the study is to conduct air audit in an industry indigenously without involving the third party. With aid of advanced tools and applications as described in the paper, the proposed system will certainly help the industries to understand the need and nuances of air audit system for compressors.